STRATEGI PENGELOLAAN RUMAH PEMOTONGAN HEWAN RUMINANSIA (RPH-R) MOPAHDALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MERAUKE - Anthonia Lobwaer; Cepi Pahlevi; Andi Ratna Sari Dewi (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2019)
Government policies that restrict imports of beef also lead to high domestic beef prices. This study aims to identify internal and external strategic factors that become strengths, weaknesses, opportunities and threats and formulate the right strategy for the management of RPH-R Mopah in increasing the PAD of Merauke Regency. This research uses descriptive approach with qualitative and quantitative research type. Qualitative methods will be used in the stage of collecting various data required and reduce the gnats in accordance with the needs of this research then at the stage of the analysis will use quantitative methods. The results of research indicate the strategic factors that become the strength is Access to information and regulation, Financing and infrastructure facilities. the number and skills of officers pengolala and socialization and promotion are the strategic factors that become weaknesses. market, regulation, technological development of animal husbandry and area potency are stratgeis factors which give opportunity to increase retribution of RPH-R Mopah as one of source of PAD and transportation outside Merauke Regency become strategic factors become threat. Alternative strategies obtained in this study can be ranked based on the highest attractiveness to the lowest as follows: Increase in Number and Skills of Human Resources (7.70), Improved Supervision of Cutting and Circulation of Meat (7.60), Regulatory Improvement (7,13) Socialization and Promotion Efforts (6.43), Addition of Other PAD Source from RPH-R Mopah (5.82) and Addition of Operating hours (5.83).